1989
DOI: 10.1039/p19890001319
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 1-aminoalkylphosphinic acids. Part 2. An alkylation approach

Abstract: Aminomethylphosphinic acid ( 7 ) , protected at nitrogen as the imine derived from benzophenone and at phosphorus as the diethylacetal and ethyl ester [i.e. (6)], undergoes facile LDA-induced alkylation. Treatment with primary alkyl halides affords, on product hydrolysis, a versatile route to phosphinic analogues of or-amino carboxylic acids. Analogues of alanine, valine, leucine, phenylalanine, tyrosine, histidine, and aspartic and glutamic acids are thus prepared; the phosphonic histidine analogue (23b) can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
45
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 5 publications
0
45
0
Order By: Relevance
“…Neither the method by Baylis et al [57] nor the most recently described preparation [58] were successful in our hands. Therefore, a third procedure [59,60] was attempted and proved to be successful. Thus, reaction of ethyl (diethoxymethyl)phosphinate [61,62] with 1,3,5-(diphenylmethyl)-hexahydro-s-triazine [57] followed by complete deprotection with concentrated aqueous HBr gave the desired compound 2 a.…”
Section: Resultsmentioning
confidence: 98%
“…Neither the method by Baylis et al [57] nor the most recently described preparation [58] were successful in our hands. Therefore, a third procedure [59,60] was attempted and proved to be successful. Thus, reaction of ethyl (diethoxymethyl)phosphinate [61,62] with 1,3,5-(diphenylmethyl)-hexahydro-s-triazine [57] followed by complete deprotection with concentrated aqueous HBr gave the desired compound 2 a.…”
Section: Resultsmentioning
confidence: 98%
“…[5] Of the many phosphorus compounds, phosphinic acids are increasingly being used in peptidomimetic design. [6,7] It has been shown that these pseudopeptides are transition-state analogue inhibitors of peptidases and in this role they are typically tightly binding and specific. [8][9][10] From the simplest starting materials, hypophosphorous acid (H 3 PO 2 ), the synthesis of phosphinic-containing molecules requires the formation of two P-C bonds.…”
Section: Introductionmentioning
confidence: 99%
“…New reactions are continuously being developed for the efficient synthesis of such compounds. [11,12] However, most of the methods reported for their preparation are not general and suffer from severe limitations: [7,13] A large excess of reagents, the direct formation of symmetrical dialkylphosphinate or the instability and handling difficulties of the starting materials. Thus, new methods using more general and milder conditions are required to allow the preparation of functionalized dialkylphosphinates.…”
Section: Introductionmentioning
confidence: 99%
“…In this connection elaboration of convenient synthetic approaches to phosphine analogs of peptides is a prospective route to potentially physiologically active compounds [335]. The synthesis of the aminoalkylphosphonous component, that forms the first phosphorus3carbon bond, has been satisfactorily developed [9,10]. In this case, the synthesis of component B requires introduction of protective groups both to the nitrogen and phosphorus ÄÄÄÄÄÄÄÄÄÄÄÄ 1 For communication III, see [1].…”
mentioning
confidence: 99%
“…In this case, the synthesis of component B requires introduction of protective groups both to the nitrogen and phosphorus ÄÄÄÄÄÄÄÄÄÄÄÄ 1 For communication III, see [1]. atoms and consists of three or four steps [9,10]. The synthesis of the pseudopeptide fragment, that forms the second phosphorus3carbon bond, most commonly involves the addition of silyl esters of aminoalkylphosphonous acids to acrylates by the procedure in [11].…”
mentioning
confidence: 99%